2016
DOI: 10.1016/j.neuropharm.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of contextual fear extinction by chronic nicotine and withdrawal from chronic nicotine is associated with hippocampal nAChR upregulation

Abstract: Chronic nicotine and withdrawal from chronic nicotine have been shown to be major modulators of fear learning behavior. Moreover, recent studies from our laboratory have shown that acute nicotine impaired fear extinction and safety learning in mice. However, the effects of chronic nicotine and withdrawal on fear extinction are unknown. Therefore, the current experiments were conducted to investigate the effects of chronic nicotine as well as withdrawal from chronic nicotine on contextual fear extinction in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 59 publications
1
18
0
Order By: Relevance
“…Therefore, the lack of an effect of chronic nicotine on backward trace conditioned safety is consistent with our interpretation that acute nicotine facilitates a maladaptive hippocampus-dependent trace US–CS association. A caveat is that only a single dose of nicotine was tested, but this dose falls within a range of doses resulting in similar plasma nicotine and cotinine levels as observed in active human smokers (Cole et al, 2014; Hukkanen et al, 2005; Kutlu et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lack of an effect of chronic nicotine on backward trace conditioned safety is consistent with our interpretation that acute nicotine facilitates a maladaptive hippocampus-dependent trace US–CS association. A caveat is that only a single dose of nicotine was tested, but this dose falls within a range of doses resulting in similar plasma nicotine and cotinine levels as observed in active human smokers (Cole et al, 2014; Hukkanen et al, 2005; Kutlu et al, 2016b). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, extinction of contextual fear conditioning is impaired by acute and chronic nicotine and during withdrawal (Kutlu, Oliver, Huang, Liu‐Chen, & Gould, ). This impairment is mediated by β 2 ‐containing nAChRs and associated with upregulation of nAChRs in hippocampus (Kutlu et al., ; Portugal, Kenney, & Gould, ). ABT‐089A, a partial agonist of α 4 β 2 ‐containing nAChRs, but not an α 7 agonist, reversed this well‐known withdrawal‐induced deficit in fear extinction (Yildirim, Connor, & Gould, ).…”
Section: Regulation Of Fear and Anxiety By Nicotine Nachrs And Bla mentioning
confidence: 99%
“…Studies in knock-out mice indicate that b 2 -containing nAChRs mediate these acute effects of nicotine (Davis & Gould, 2007; for review : Kutlu & Gould, 2015). In contrast, extinction of contextual fear conditioning is impaired by acute and chronic nicotine and during withdrawal (Kutlu, Oliver, Huang, Liu-Chen, & Gould, 2016). This impairment is mediated by b 2 -containing nAChRs and associated with upregulation of nAChRs in hippocampus (Kutlu et al, 2016;Portugal, Kenney, & Gould, 2008).…”
Section: Regulation Of Fear and Anxiety By Nicotine Nachrs And Bla mentioning
confidence: 99%
“…For acute and chronic nicotine extinction, a 2-way ANOVA (drug × extinction day) was conducted on normalized freezing levels (freezing × 100/initial freezing), wherein extinction day was treated as a repeated measure. Freezing was normalized to ensure differences in baseline freezing did not affect subsequent freezing curves (Tian et al, 2008; Kutlu et al, 2016b). Planned comparisons of extinction across doses were made using Bonferroni-corrected t-tests.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that acute nicotine enhances contextual fear learning in male and female mice (Gould, 2003; Gould et al, 2004; Gould & Wehner, 1999). In male mice, acute nicotine has been shown to impair contextual fear extinction, stunting the normal decline of the fear response across extinction trials without affecting general freezing behavior (Kutlu & Gould, 2014; Kutlu et al, 2016a; 2017a,b) and enhance spontaneous recovery of extinguished contextual fear (Kutlu et al, 2016b). Chronic nicotine has similar effects on contextual fear learning process.…”
Section: Introductionmentioning
confidence: 99%